The Influence of Household Consumption and the Human Development Index on Economic Growth in West Java - Hugo Aries Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
The aim of this research is to determine the influence of household consumption and the human development index (HDI) on economic growth in West Java. HDI is a requirement for sustainable economic development. Without skilled human resources, Indonesia will be left behind by other countries. Likewise, household consumption plays an important role in Indonesia's development. Good consumption will have an impact on the economy. This method uses quantitative methods. Data taken from the Central Statistics Agency, data X1 (Household Consumption) and X2 (Human Development Index) and Y (Economic Growth) in West Java. Data in West Java covers the city of Bekasi, Bekasi Regency, Cimahi, Tasikmalaya and Cianjur for 10 years from 2008 to 2018. Data were processed using SPSS 21. Test assumptions by carrying out normality, collinearity, Heteroscedasticity, Anova and Rsquare table tests with tests. linear regression. The research results show that household consumption influences economic growth in West Java, HDI influences economic growth, and household consumption and HDI together influence economic growth. Central and regional governments can work together to expand the workforce and improve human resources.